2021
DOI: 10.1155/2021/1901887
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Knowledge, Attitude, and Behavior of Dentists on HIV/AIDS in West Java, Indonesia, in the COVID-19 Era

Abstract: Purpose. HIV/AIDS is still a serious public health problem in Indonesia. It has been concerned that the coronavirus disease 2019 (COVID-19) pandemic has a serious impact on people living with HIV (PLWH). Therefore, dentists remain to have a significant role to play in the overall healthcare delivery to PLWH and reducing new HIV infections. The purpose of this study was to assess the knowledge, attitudes, and behavior of dentists in West Java about HIV/AIDS in the COVID-19 era. Methods. This cross-sectional stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 29 publications
0
11
1
Order By: Relevance
“…With regard to the tropical infectious diseases and oral health, there were three types of surveys exploring knowledge mastery of medical and dental providers. Firstly, most research reported the knowledge and attitude of medical or dental professionals towards infectious diseases, such as AIDS [ 23 , 24 ], hepatitis [ 25 , 26 ], COVID [ 27 , 28 ], leprosy [ 29 , 30 ] and some other tropical diseases [ 31 , 32 ]. However, few of them concentrated on their oral manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the tropical infectious diseases and oral health, there were three types of surveys exploring knowledge mastery of medical and dental providers. Firstly, most research reported the knowledge and attitude of medical or dental professionals towards infectious diseases, such as AIDS [ 23 , 24 ], hepatitis [ 25 , 26 ], COVID [ 27 , 28 ], leprosy [ 29 , 30 ] and some other tropical diseases [ 31 , 32 ]. However, few of them concentrated on their oral manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the authors found that despite having a high HIV/AIDS knowledge, there is an overall negative attitude towards people living with HIV/AIDS (PLWHA) (i.e., 60.28%), thus showing that a high proportion of people with knowledge does not translate to more positive attitudes. Contrarily, another Indonesian study among 209 dentists found that only about 44% had good knowledge of HIV/AIDS, though slightly more than half the sample (53%) had a positive attitude towards PLWHA [ 32 ]. The authors agreed that the attitude score is deemed low (negative) considering that the cohort under-study is HCW, and thus they should be less discriminatory in treating PLWHA.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, results based on participants’ occupation status revealed healthcare professionals, including medical students, to have a higher level of knowledge, awareness, attitude, and perception—a pattern that is absolutely expected considering their background [ 11 , 14 , 17 , 32 ]. Contrarily, the knowledge level was found to be extremely low among professions such as industrial workers (migrants) [ 42 ] and sex workers [ 29 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…In another study in West Java, it was revealed that the attitudes, knowledge and behavior of dentists concerning HIV/AIDS still require to be escalated and balanced. HIV/AIDS education and training programs for dentists are still demanded to increase knowledge and awareness, eliminate stigma and discrimination associated with HIV, and support disease prevention and control in the COVID-19 era [14].…”
Section: Discussionmentioning
confidence: 99%